1982
DOI: 10.1007/bf00926910
|View full text |Cite
|
Sign up to set email alerts
|

Uracil synthesisvia HCN oligomerization

Abstract: Uracil is released from HCN oligomers upon acid hydrolysis in concentrations of 0.001% for 1 M HCN solutions to 0.005% for 0.1 M solutions. This yield is comparable with earlier reported, minor or nonbiological pyrimidines such as 5-hydroxyuracil and orotic acid. This is the first report of uracil itself via HCN oligomerization. Data are presented which establish that the observed uracil is not formed by decarboxylation of previously formed orotic acid, but via acid hydrolysis of at least two other precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Dihydrouracil (DHU) was synthesized from /~-alanine and urea under mild conditions and was further dehydrogenated by UV-irradiation on various supports to produce uracil (Chittenden and Schwartz, 1976). Hydrolysis of HCN oligomers produced 4,5-dihydroxypyrimidine, orotic acid, 5-hydroxyuracil and uracil as well as adenine and amino acids (Ferris et al, 1978b;Voet and Schwartz, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Dihydrouracil (DHU) was synthesized from /~-alanine and urea under mild conditions and was further dehydrogenated by UV-irradiation on various supports to produce uracil (Chittenden and Schwartz, 1976). Hydrolysis of HCN oligomers produced 4,5-dihydroxypyrimidine, orotic acid, 5-hydroxyuracil and uracil as well as adenine and amino acids (Ferris et al, 1978b;Voet and Schwartz, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Among the prebiotic sources of this pyrimidine would have been meteoritic impacts and the hydrolysis of HCN oligomers. [13,14] The levels of uracil are consistent with an evaporating lagoon venue, since the thermal stability of this heterocycle was an important criterion in the experimental design. Huber and Wächtershäuser have suggested that thioacetic acid might be formed from methanethiol and carbon monoxide on a metal sulfide.…”
Section: Introductionmentioning
confidence: 83%
“…In this latter case, the reduction of two exocyclic imino moieties on the pyrimidine ring was a specific redox step to obtain the C-5/C-6 double bond in pyrimidine nucleobases. As an alternative, purines can be synthesized by a multi-steps process involving HCN oligomers, 5-imidazole carbonitrile and 5-imidazole carboxyamide (not shown), that are also key (Sanchez et al 1966;Voet and Schwartz 1983;Schwartz and Bakker 1989;Saladino et al 2007).…”
Section: Synthesis Of Nucleic Acid and Heterocycle Derivativesmentioning
confidence: 99%